2006
DOI: 10.1038/sj.bjc.6603196
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II study of docetaxel and S-1 in patients with advanced gastric cancer

Abstract: The aims of this phase I/II study of docetaxel and S-1 were to determine the dose-limiting toxicity (DLT), maximum-tolerated dose (MTD), and recommended dose (RD) in the phase I part and to explore the tumour response, survival and safety in the phase II part. Patients with histologically-or cytologically confirmed unresectable or recurrent gastric cancer were eligible. Treatment consisted of intravenous docetaxel on day 1 (starting dose 50 mg m À2 ) and oral S-1 at a fixed dose of 40 mg m À2 twice daily on da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
41
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 25 publications
(30 reference statements)
5
41
2
Order By: Relevance
“…Ajani et al (2005) reported that a combination of docetaxel, cisplatin, and fluorouracil is highly active against advanced untreated gastric or gastroesophageal adenocarcinoma. Docetaxel has also been combined with TS-1, and available evidence indicates that this combination is effective and well tolerated in patients with advanced gastric cancer (Yamaguchi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Ajani et al (2005) reported that a combination of docetaxel, cisplatin, and fluorouracil is highly active against advanced untreated gastric or gastroesophageal adenocarcinoma. Docetaxel has also been combined with TS-1, and available evidence indicates that this combination is effective and well tolerated in patients with advanced gastric cancer (Yamaguchi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The recent introduction of a new oral drug, S-1 (Shirasaka et al, 1996), which was developed on the basis of biochemical modulation to inhibit dihydropyrimidine dehydrogenase and orotate phosphoribosyltransferase to therapeutic modality for gastric cancer, has enabled us to increase ORR to 46 -74% and MST to 10.9 -14.8 months by its combination with cisplatin (CDDP), docetaxel or CTP-11, with less toxicity than 5-FU (Koizumi et al, 2003;Ajani et al, 2006;Inokuchi et al, 2006;Yamaguchi et al, 2006).…”
mentioning
confidence: 99%
“…In combination with CDDP, 5-FU or CDDP plus 5-FU or S-1, docetaxel has shown a higher ORR of 37 to 56% and MST of 9.0 to 14.3 months (Roth et al, 2000;Thuss-Patience et al, 2005;Van Cutsem et al, 2006;Yamaguchi et al, 2006).…”
mentioning
confidence: 99%
“…[5][6][7] Docetaxel showed synergism with S-1 in vitro, and the response rate was 46%-67% in several phase 2 trials. [9][10][11] Based on these findings, we designed a randomized phase 2 study to determine whether S-1 or cisplatin shows greater promise as a combination partner of docetaxel for a subsequent phase 3 study. We adopted a weekly docetaxel regimen to assess whether split administration improves drug tolerability and tested the predictive values of biomarkers for treatment-related outcomes.…”
mentioning
confidence: 99%